Educational Centers and their Role in Scientific Research Advancement in Iraqi society - Hassani Al Douri, Khaled Hamo; Ali, Thawrah Khattab (Journal of Tikrit University for Humanities, 2022)
Iraq has been known since antiquity for its ancient cultural and scientific heritage that extends since the middle of the fourth millennium BC when it discovered writing. This legacy continued with its development and the breadth of its achievements to present to the world the first educational institutions, Hammu Rabi (1792_1750 BC) who established two schools, the first one is in Spar and the second one is in Kish. Iraq presented the world with the oldest legal legislation and issued four laws that are rightfully the oldest and most complete laws discovered so far My research titled (educational centers and their role in the scientific research advancement in the Iraqi society) aims to clarify the educational means in Iraq, their role and impact on contemporary and future generations and urging them to provide the best. Based on the importance of what we mentioned, the Iraqi person has proven his ability to communicate with the past and draw inspiration from his cultural heritage to build his present and its future, especially those related to the educational and academic aspect.